Very late unusual thrombosis of the remnant pulmonary vasculatures after lung resection complicated by embolic events - Hyun Ju Yoon; Kye Hun Kim; Myung Ho Jeong; Jeong Gwan Cho; Jong Chun Park (Journal of Cardiothoracic Surgery, 2019)
Abstract Background Primary thrombosis of the pulmonary vasculatures without extra-pulmonary sources of embolism are uncommon. Here, we report 2 cases of thrombosis of the stump of the remnant pulmonary vasculatures after lung resection complicated by embolic events with review of the literature. Case presentation A 75-year-old female was consulted to evaluate cardiac source of embolism for acute cerebral infarction. The patient underwent left upper lobectomy because of lung cancer 2 years ago. Cardiovascular imaging revealed about 1.6 cm × 1.4 cm sized thrombus within the remnant stump of the left superior pulmonary vein. The patient was treated by anticoagulation with warfarin, because the patients refused surgical removal of thrombus. A 57-year-old female who had a history of right pneumonectomy 10 years ago presented with dyspnea. Cardiovascular imaging revealed 1.7 × 1.5 cm sized thrombus in the right pulmonary artery stump and small pulmonary embolism in the left lower segmental pulmonary artery. The patient was treated by long-term anticoagulation with warfarin, and the thrombus and pulmonary embolism were resolved. Conclusion The present cases demonstrated that very late thrombosis of the remnant pulmonary vascular structures and subsequent fatal embolic complications can develope even several years later after lung resection. Therefore, the dead space of the remnant vascular structures should be minimized during lung resection surgery, and the developement of delayed thromboembolic complications associated with vascular stump thrombosis should be carefully monitored.